Talent Management: Key to Organisation’s Success - Dahagam, Srikanth; Pingle, Dr Sameer (The journal of contemporary issues in business and government, 2023)
Every organisation aims to be future fit and makes investments in various strategic areas which also includes Talent Management. There is always a tussle for grabbing the right talent in the talent-hungry environment. So there is always some pressure on the organization attract, evaluate, develop and retain talented workforce. Talent management is indispensable for survival and sustainable development of any organization.Talent management involves identifying the potential talents and preparing them for possible future roles in the Organisation. In the battle of talents, organizations should use Talent Management as a Strategic weapon, if talent has to be won in this battle. Managing and developing talent requires relentless efforts and willpower on the part of top management. Considering the business landscape, business strategy, organization’s communication channels organization’s culture and values, resources availability and allocation, each organization adopts any established talent management model or even can develop its own talent management model. However, the focus must be to build a talent model that is unique to that organization that meet all compliances of its business operations. Ideally any talent management model should manage organization’s internal and external talent pool and address workforce related issues. In this paper, authors have reviewed the various models proposed by well-known consulting, business and academic organisations across the globe. These prove that, the organisations which are committed to Talent management have competitive advantage over their peers.